Social autopsy analysis of the determinants of neonatal and under-five mortalities in Nigeria, 2013-2018 - Robinson D Wammanda; John Quinley; George I Eluwa; Adeyinka Odejimi; Michael Kunnuji; William Weiss; Inuwa B Jalingo; Olorunimbe T Ayokunle; Alice R Nte; Rebekah King; Ana C Franca-Koh (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Nigeria suffers from one of the world's highest child mortality rates, with about 900,000 deaths in a single year, despite being classified as a middle-income country. Over the past few years, substantial efforts have been made to reduce child mortality, with under-five mortality declining by 31.6% between 1990 and 2018. However, this decline is slower than needed to reduce child mortality significantly. This study presents the social autopsy component of the 2019 verbal and social autopsy (VASA) survey to provide an in-depth understanding of the social determinants of under-five mortality in Nigeria. # Methods The study was a cross-sectional inquiry into the social determinants of neonatal and 1-59 months child deaths from the 2018 Nigeria Demographic and Health Survey (NDHS) weighted to represent the Nigerian population. The social autopsy survey asked about maternal care for neonates and 1-59 months children during the final illness. # Results Child mortality in Nigeria in children aged 1-59 months is strongly associated with levels of wealth, place of residence, and maternal education. The association of these same socio-economic factors with neonatal mortality is weaker. While there were significant associations with wealth quintiles and geopolitical zones, higher maternal education was not significantly associated with lower neonatal death rates. Maternal complications in pregnancy and/or labour and delivery were common and strongly associated with stillbirths and deaths in the first two days. Severity scores at the inception of the illnesses did not show differences between children who only received informal care versus those who went to formal care providers. The main barriers to care were distance, cost, transport, and the need to travel at night, and these barriers were interlinked. More distant facilities usually required vehicle transport, which was expensive for low-income families. Travelling for an emergency at night was even more difficult in terms of finding and paying for transport and involving problems with insecurity and bad roads. # Conclusions The family, community, and health system factors related to neonatal and 1-59 months child deaths in Nigeria were highlighted in this study. Deaths were commonly associated with numerous factors, each of which could contribute to the sequence of events resulting in a preventable death.